1990
DOI: 10.1037/0012-1649.26.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Sound localization acuity in very young infants: An observer-based testing procedure.

Abstract: Infants 8 to 28 weeks of age were tested to determine the smallest sound shift off midline and along the horizontal axis that could be reliably discriminated, that is, minimum audible angle. Both soundshift and no-shift trials were presented. For each trial, an observer decided, based solely on the infant's behavior, whether the sound shifted location (i.e., an observer-based yes-no task). To isolate sensory from nonsensory factors, analyses were performed on d' scores. The results indicated increasing localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…On the other hand, the acceptable level of noise in a child's environment is often determined by an adult whose judgment is based on his or her own experience. Developmental improvements in binaural hearing, shown here and elsewhere (Nozza 1987;Morrongiello et al 1990;Moore et al 1991), suggest that children will be relatively more disadvantaged by a given background noise level than adults. It appears that the fluctuating nature of OME may adversely affect the normal pattern of development for binaural hearing.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the acceptable level of noise in a child's environment is often determined by an adult whose judgment is based on his or her own experience. Developmental improvements in binaural hearing, shown here and elsewhere (Nozza 1987;Morrongiello et al 1990;Moore et al 1991), suggest that children will be relatively more disadvantaged by a given background noise level than adults. It appears that the fluctuating nature of OME may adversely affect the normal pattern of development for binaural hearing.…”
Section: Discussionmentioning
confidence: 96%
“…Head orientation research provided reliable results (see Goren et al, 1975;Maurer and Young, 1983). Studies investigating sound localization (Field et al, 1980;Morrongiello et al, 1990;Muir, 1985) have reported that neonates can shift their eyes and heads in the direction of a sound quickly and accurately.…”
Section: Procedures and Designmentioning
confidence: 93%
“…There are only a few studies devoted to spatial hearing in infants (localisation accuracy: Muir and Field 1979;Muir et al , review 1989Muir and Clifton 1985; for review, see Muir and Hains 2004;Morrongiello and Rocca 1987;MAA: Ashmead et al 1987;Morrongiello 1988;Morrongiello et al 1990) and young children (localisation accuracy: Van Deun et al 2009;Grieco-Calub and Litovsky 2010;Lovett et al 2012;Kühnle et al 2012;Otte et al 2013;MAA: Morrongiello 1988;Litovsky 1997;Lovett et al 2012;Kühnle et al 2012).…”
Section: Infants Children and Adolescentsmentioning
confidence: 97%